Analysis of the Effect of Winding Wire Cross-sectional Area and Rotating Speed on the Efficiency of 18 Slot 16 Pole Permanent Magnet Synchronous Generator - Delafena, Irfan; Liliana, Liliana (PROtek : Jurnal Ilmiah Teknik Elektro, 2024)
The potential of renewable energy in Indonesia is very large with a total of 3,643.0 GW. One of them is wind energy, the huge potential of wind energy which is 154.9 GW is very wasted if it is not optimized as well as possible. The biggest obstacle to utilizing wind potential is low wind speed in some areas in Indonesia. So an effective generation system is needed to produce efficient output. A permanent Magnet Synchronous Generator (PMSG) is very suitable for use in areas of potential low-speed winds because low rotation can produce good efficiency. The output value of the Permanent Magnet Synchronous Generator (PMSG) is currently still low and can still be improved, for this research will analyze the broad influence of the cross-section of the winding wire on the stator on the efficiency of the 18 slots 16 poles Permanent Magnet Generator with rotational speed based on wind speed in Indonesia. Variations were carried out on a cross-sectional area of 0.6 mm2-3.6 mm2 winding wire and rotating speeds of 500 rpm, 750 rpm, and 1000 rpm. By using MagNet Infolytica 7.5 software based on Finite Element Method (FEM) to obtain output values in the form of voltage, current, and torque.Â  For efficiency values, data is reprocessed using Microsoft Excel. The results of this study show that the value of efficiency increases. The best efficiency produced when the rotating speed is 500 rpm is 97.04% at a cross-sectional area of 2.6 mm2 winding wire, for a rotating speed of 750 rpm the efficiency reaches 97.24% at a cross-sectional area of 2.4 mm2 winding wire and at a rotating speed of 1000 rpm the resulting efficiency is 97.16% at a cross-sectional area of 2.4 mm2 winding wire.